2012
DOI: 10.3748/wjg.v18.i24.3156
|View full text |Cite
|
Sign up to set email alerts
|

Two-stagevssingle-stage management for concomitant gallstones and common bile duct stones

Abstract: Single-stage management is equivalent to two-stage management but requires fewer procedures. However, patient's condition, operator's expertise and local resources should be taken into account in making treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
86
2
12

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(106 citation statements)
references
References 42 publications
6
86
2
12
Order By: Relevance
“…Postoperative minor complications occurred in three patients (12.5%): mild pancreatitis with elevation of serum amylase in two patients and minor bile leak in one patient; no mortality, nearly in agreement with several studies that reported morbidity and mortality rates of 5-11 and 8-12%, respectively [9].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Postoperative minor complications occurred in three patients (12.5%): mild pancreatitis with elevation of serum amylase in two patients and minor bile leak in one patient; no mortality, nearly in agreement with several studies that reported morbidity and mortality rates of 5-11 and 8-12%, respectively [9].…”
Section: Discussionsupporting
confidence: 74%
“…A similar study carried out by Alexakis and Connor denoted a success rate of 80-91% [15]. In another study by Lu et al, success rates of 89-95% were reported [9]. Dasari et al reported success rate in 72/81 (91%) patients [16].…”
Section: Discussionmentioning
confidence: 62%
“…Over these years, randomized controlled trials showed superior outcome with LCBDE compared with endoscopic or OCBDE treatment for CBD stones. It is associated with a high stone clearance rate ranging from 84-97 %, a postoperative morbidity rate of 4-16 %, and a mortality rate of approximately 0-0.8 % [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, one recent prospective trial comparing LCBDE and open surgery confirmed the superiority of the laparoscopic method in terms of efficiency, morbidity and mortality [78] . When comparing the two-stage (LC with preoperative or postoperative ERCP) and single-stage (LC with LCBDE), no significant differences were found, except for some intrinsic characteristics (fewer therapeutic sessions) [79,80] . Another trial [81] reported having a reduced hospital stay when using LCBDE.…”
Section: Concomitant Laparoscopic Cholecystectomy and Common Bile Ducmentioning
confidence: 97%